Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

La politique sexuelle de la féminité noire - Hill Collins, Patricia (La pensee feministe noire : savoir, conscience et politique de l'empowerment, 2016)
Traduction de : Black feminist thought. Traduit de l'anglais (Etats-Unis) par Diane Lamoureux.
Keywords: afro-féminisme; amériques; approches et analyses; cours; empowerment; féminismes noirs; intersectionnalité; premier cycle; ressource en ligne; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; états-unis